The lignan niranthin poisons Leishmania donovani topoisomerase IB and favours a Th1 immune response in mice - Sayan Mullick Chowdhury; Tulika Mukherjee; Rupkatha Mukhopadhyay; Budhaditya Mukherjee; Souvik Sengupta; Sharmila Chattopadhyay; Parasuraman Jaisankar; Syamal Roy; Hemanta K. Majumder (2012)
Research Article2 October 2012Open Access The lignan niranthin poisons Leishmania donovani topoisomerase IB and favours a Th1 immune response in mice Sayan Chowdhury Sayan Chowdhury Molecular Parasitology Laboratory, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Tulika Mukherjee Tulika Mukherjee Department of Chemistry, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Rupkatha Mukhopadhyay Rupkatha Mukhopadhyay Infectious Diseases and Immunology Division, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Budhaditya Mukherjee Budhaditya Mukherjee Infectious Diseases and Immunology Division, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Souvik Sengupta Souvik Sengupta Molecular Parasitology Laboratory, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Sharmila Chattopadhyay Sharmila Chattopadhyay Drug Development Diagnostics and Biotechnology Division, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Parasuraman Jaisankar Parasuraman Jaisankar Department of Chemistry, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Syamal Roy Syamal Roy Infectious Diseases and Immunology Division, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Hemanta K. Majumder Corresponding Author Hemanta K. Majumder [email protected] Molecular Parasitology Laboratory, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Sayan Chowdhury Sayan Chowdhury Molecular Parasitology Laboratory, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Tulika Mukherjee Tulika Mukherjee Department of Chemistry, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Rupkatha Mukhopadhyay Rupkatha Mukhopadhyay Infectious Diseases and Immunology Division, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Budhaditya Mukherjee Budhaditya Mukherjee Infectious Diseases and Immunology Division, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Souvik Sengupta Souvik Sengupta Molecular Parasitology Laboratory, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Sharmila Chattopadhyay Sharmila Chattopadhyay Drug Development Diagnostics and Biotechnology Division, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Parasuraman Jaisankar Parasuraman Jaisankar Department of Chemistry, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Syamal Roy Syamal Roy Infectious Diseases and Immunology Division, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Hemanta K. Majumder Corresponding Author Hemanta K. Majumder [email protected] Molecular Parasitology Laboratory, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India Search for more papers by this author Author Information Sayan Chowdhury1, Tulika Mukherjee2, Rupkatha Mukhopadhyay3, Budhaditya Mukherjee3, Souvik Sengupta1, Sharmila Chattopadhyay4, Parasuraman Jaisankar2, Syamal Roy3 and Hemanta K. Majumder *,1 1Molecular Parasitology Laboratory, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India 2Department of Chemistry, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India 3Infectious Diseases and Immunology Division, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India 4Drug Development Diagnostics and Biotechnology Division, Indian Institute of Chemical Biology, Jadavpur, Kolkata, India *Tel: +91 33 2412 3207; Fax: +91 33 2473 5197 EMBO Mol Med (2012)4:1126-1143https://doi.org/10.1002/emmm.201201316 PDFDownload PDF of article text and main figures. Peer ReviewDownload a summary of the editorial decision process including editorial decision letters, reviewer comments and author responses to feedback. ToolsAdd to favoritesDownload CitationsTrack CitationsPermissions Figures & Info Abstract Niranthin, a lignan isolated from the aerial parts of the plant Phyllanthus amarus, exhibits a wide spectrum of pharmacological activities. In the present study, we have shown for the first time that niranthin is a potent anti-leishmanial agent. The compound induces topoisomerase I-mediated DNA–protein adduct formation inside Leishmania cells and triggers apoptosis by activation of cellular nucleases. We also show that niranthin inhibits the relaxation activity of heterodimeric type IB topoisomerase of L. donovani and acts as a non-competitive inhibitor interacting with both subunits of the enzyme. Niranthin interacts with DNA–protein binary complexes and thus stabilizes the ‘cleavable complex’ formation and subsequently inhibits the religation of cleaved strand. The compound inhibits the proliferation of Leishmania amastigotes in infected cultured murine macrophages with limited cytotoxicity to the host cells and is effective against antimony-resistant Leishmania parasites by modulating upregulated P-glycoprotein on host macrophages. Importantly, besides its in vitro efficacy, niranthin treatment leads to a switch from a Th2- to a Th1-type immune response in infected BALB/c mice. The immune response causes production of nitric oxide, which results in almost complete clearance of the liver and splenic parasite burden after intraperitoneal or intramuscular administration of the drug. These findings can be exploited to develop niranthin as a new drug candidate against drug-resistant leishmaniasis. The paper explained PROBLEM: Leishmaniasis is a fatal disease affecting mostly underdeveloped countries worldwide with a high mortality rate and limited treatment options due to the development of drug resistance. Overexpression of surface transporters, like P-glycoprotein (P-gp), associated with resistant parasite infection, effluxes the antimony content from the cell. This restricts the use of commonly used drugs like pentostam or sodium stibogluconate. An alternative treatment strategy with a novel therapeutic target is required for the radical cure of leishmaniasis. RESULTS: Our studies define for the first time that niranthin stabilizes the covalent parasite topoisomerase I-DNA complex in vivo and in vitro and hampers all DNA-related transactions, which ultimately forces the parasite to die. We have determined that niranthin is a promising anti-leishmanial agent against experimental visceral leishmaniasis and a good immunomodulator since niranthin expands the Th1-type immune response with almost sterile protection in mice. IMPACT: The major implication of this study is the potential to combat the emergence of drug resistant Leishmania donovani. In vitro efficacy of downregulation of P-gp on the macrophage surface along with in vivo sterile protection provides a possible approach for treatment. Targeting topoisomerase I of the parasite along with a Th2 to Th1 switch provides its dual mode of inhibition. Our studies are expected to open up new avenues for clinical trials with conventional sodium antimony gluconate as a combination therapy as well as parallel treatment. INTRODUCTION Leishmaniasis is one of the most serious forms of parasitic diseases caused by the protozoan flagellates of the genus Leishmania. The disease presents a spectrum of clinical manifestations (Olivier et al, 2005) ranging from ulcerative skin lesions developing at the site of the sandfly bite (localized cutaneous leishmaniasis) to the most destructive mucosal inflammation and disseminated visceral infection (Reithinger et al, 2007). More than 350 million people are at risk of the infection and the disease causes about 70,000 deaths each year globally (Kaye & Scott, 2011). To date, there is no vaccine against any form of human leishmaniasis (Nagill & Kaur, 2011). For the last six decades, organic pentavalent antimonials [Sb (V)] have been the first line drugs for the treatment of this disease and emergence of resistant clinical isolates to these drugs pose a serious obstacle for disease control and treatment (Ashutosh & Goyal, 2007). Alternative medicines like amphotericin B (Wortmann et al, 2010) or miltefosine (Rahman et al, 2011) are in phase IV trials despite their costliness and teratogenicity. Thus, the identification of new molecular targets for improved therapy of Leishmania infection is vital. DNA topoisomerases are ubiquitous DNA-manipulating enzymes, which catalyse the breakage and rejoining of DNA strands to modulate the dynamic nature of DNA secondary and higher order structures in various vital life processes involving DNA transactions (Liu, 1989; Wang, 1996). Topoisomerases can be classified into two groups based on their DNA processing abilities: type I and type II, both of which are of equal importance as chemotherapeutic targets (Fortune & Osheroff, 2006; Pommier, 2006). In contrast to other eukaryotic topoisomerases, L. donovani topoisomerase I is an unusual heterodimeric enzyme in which the core DNA binding domain ‘VAILCNH’ is located on the large subunit (LdTOP1L, 635 amino acids) and catalytic domain harbouring the catalytic ‘SKXXY’ motif is located on the small subunit (LdTOP1S, 262 amino acids; Das et al, 2004). DNA topoisomerases have emerged as principal therapeutic targets and targeting agents have a broad spectrum of anti-parasitic activity. These inhibitors can be broadly classified into two classes. The class I inhibitors stabilize the formation of topoisomerase–DNA covalent complex (cleavable complex) and are ‘topoisomerase poisons’ while the inhibitors, which abrogate only the catalytic property of the enzyme and thus interfere with the formation of ‘covalent complex’ formation are called ‘class II inhibitors’ (Chowdhury et al, 2011). The lignan family of natural products includes compounds with important anti-neoplastic and anti-viral properties. Podophyllotoxin and two other semisynthetic derivatives, etoposide and teniposide, are common amongst them, and they show a wide variety of anti-cancer properties (Gordaliza et al, 2000) by inhibiting topoisomerase II and microtubule assembly (Hartmann & Lipp, 2006; Imbert, 1998). The lignan-rich fraction from aerial parts of Phyllanthus amarus exhibits cytotoxic effects in the K-562 cell line and contains niranthin, which has the most potent inhibitory activity (Leite et al, 2006). Niranthin also exhibits anti-inflammatory and anti-allodynic properties (Kassuya et al, 2006) and has been shown to possess anti-viral activity against human hepatitis B virus in vitro (Huang et al, 2003). In the present study, we have demonstrated for the first time that the lignan niranthin isolated from P. amarus is an anti-leishmanial agent and induces apoptotic events in the parasites. Induction of reactive oxygen species (ROS) formation and activation of nucleases lead to DNA fragmentation and the compound forms a cleavage complex with topoisomerase I of L. donovani. Our data suggest that niranthin binds with each subunit of the enzyme. This novel topoisomerase IB poison of L. donovani can efficiently reduce parasite burden in cultured macrophages infected with antimony-resistant and -sensitive parasites. Niranthin at low concentration, when combined with sodium antimony gluconate (SAG), can clear SAG-unresponsive Leishmania (GE1) by reversing multidrug resistance. In addition, as an immunomodulatory molecule in vivo, niranthin directs the immune response from the parasite-protecting Th2 to the host-protective Th1 response. This results in IL-12-driven expansion of Th1 cells and macrophage activation through the production of IFN-γ, which ultimately triggers generation of nitric oxide (NO) and ROS in macrophages and thus confers almost complete protection against leishmaniasis in BALB/c mice. Taken together, niranthin is a promising new therapeutic agent against emerging antimony-resistant strains of Leishmania. RESULTS Niranthin inhibits growth of L. donovani promastigotes by induction of apoptosis To evaluate the anti-leishmanial potential of niranthin (Fig 1A), we first investigated whether the compound induces cell death in the parasite. Promastigotes were treated with different concentrations of niranthin and cell viability measured. After 24 h, viability was reduced by 93 and 98% using 5 and 10 µM niranthin, respectively (Fig 1B). In addition, treatment with niranthin generated a fivefold higher amount of ROS compared to DMSO treatment inside the parasites (Supporting Information Fig S1). The mode of cell death in niranthin-treated parasites was investigated by fluorescein isothiocyanate (FITC)-annexinV and propidium iodide (PI) staining. Externalization of phosphatidyl serine (stained by annexinV) and presence of impermeant cell membrane (negative PI staining) are hallmarks of programmed cell death (PCD). Flow cytometry shows that 96% of DMSO-treated parasites were both PI- and annexinV-negative (Fig 1C, panel I), while 53% of niranthin-treated parasites were annexinV-positive after 6 h of drug treatment (10 µM; Fig 1C, panel II). A time-dependent increase of both FITC-annexinV-positive cells and double-positive (FITC-annexinV and PI) populations were observed (Fig 1C, panel III), which indicates that the drug-treated cells die via the apoptotic pathway. The extent of DNA fragmentation in niranthin-treated parasites was estimated using an ELISA and a time-dependent increase in niranthin-induced DNA fragmentation up to 85% at 8 h was observed (Fig 1D). This indicates that the triggering of apoptosis ultimately activates different nucleases to degrade the parasite nucleosomal structure. Figure 1. Cytotoxicity analysis and morphological and physiological changes associated with niranthin-mediated cell death. A.. Structure of niranthin. B.. Promastigotes were cultured in the presence of 0.2% DMSO (▴) or 5 µM (▪), 10 µM (♦) and 20 µM (•) of niranthin. Aliquots were taken at intervals and percentage of viable promastigotes was measured by Alamar Blue reagent. Values were taken in triplicate, averaged and plotted against time. Data represent means ± SE (n = 3). *p < 0.05, **p < 0.01 (Student's t-test). ***Indicates significant difference between DMSO control and 5, 10 or 20 µM niranthin treatment (p < 0.001) at the 12 h time-point. C.. Flow cytometric analysis of promastigote death through PCD/necrotic processes. Parasites were stained with FITC-annexinV and propidium iodide after treatment with 0.2% DMSO (panel I), niranthin (10 µM; panel II) for 6 and 8 h (panel III), respectively. D.. Extent of genomic DNA fragmentation upon niranthin treatment. Parasites were treated with 10 and 20 µM of niranthin for the indiacted time periods. As negative control, parasites were also treated with 0.2% DMSO. Values were obtained from the MULTISCAN EX readings at 405 nm. The percentage was plotted as units of time. Data represent means ± SD (n = 3). **p < 0.01 (Student's t-test). ***Indicates significant difference between DMSO control and 20 µM niranthin treatment (p < 0.001) for 4, 6 and 8 h. E.. Niranthin-mediated cell cycle arrest in L. donovani AG83 promastigote cells. Histograms of distribution of DNA content with flow cytometry in Leishmania cells. Cell cycle arrest was analysed after treatment with 0.2% DMSO as control, and with niranthin (20 µM) for 2, 4 and 8 h. Cells were then fixed and stained with propidium iodide, and nuclei were analysed for DNA content by flow cytometry. In total, 20,000 nuclei were counted from each sample. The percentages of cells within different cells stages were determined as described in Materials and Methods. Download figure Download PowerPoint With the degradation of oligonucleosomal structures and induction of apoptosis, treatment with niranthin reduces replication of the parasites and eventually slows down the active cell cycle. Untreated cells show the expected cell cycle distribution in G1, S and G2/M phases throughout the experiment (G1: 46%, S: 20% and G2/M: 34%) while treatment with niranthin caused arrest at G1 phase and inhibited entry into S phase of L. donovani promastigotes (Fig 1E). Prolonged treatment for 8 h dramatically reduces the G2/M population (11%) compared to control cells. As a result, parasite replication is hampered in a time-dependent manner (G2/M population reduced from 26 to 11%). Niranthin stabilizes topoisomerase cleavable complex formation in L. donovani promastigotes in vivo and in vitro The ability of niranthin to induce protein-linked DNA complexes, which could lead to apoptosis in the L. donovani promastigotes, was investigated by KCl-SDS precipitation assay (Bodley & Shapiro, 1995). The experiments were performed with [3H]-thymidine-labelled promastigotes, treated with various concentrations of niranthin as well as camptothecin (CPT) and dihydrobetulinic acid (DHBA) as controls. Treatment of cells with different concentrations of niranthin significantly increased the SDS–K+-precipitable complex compared with the untreated control cells (Fig 2A) and their amount was similar to that obtained by treatment with different concentrations of CPT for 8 h. These results indicated that the formation of SDS–K+ precipitable complexes is due to formation of protein-linked DNA complexes following treatment with niranthin. Pre-treatment for 30 min with 200 µM DHBA, which antagonizes topoisomerase I-mediated DNA cleavage, before incubation with niranthin prevents accumulation of precipitable complexes, which strongly suggests that their accumulation induced by niranthin is due to topoisomerase–DNA links. Figure 2. Analysis of protein linked DNA complex formation in L. donovani promastigotes. A.. Exponentially growing L. donovani promastigotes (5 × 106 cells/ml) were labeled with [3H] thymidine at 22°C for 24 h and then treated with different concentrations of niranthin and DHBA as indicated. SDS-K+ precipitable complex were measured as described in Materials and Methodss. Experiments were performed three times and representative data from one set of experiments are expressed as means ± SE. Variations among different set of experiments were <10%. *p < 0.05, **p < 0.01 (Student's t-test). ***Indicates significant difference between DHBA control and niranthin treatments (p < 0.001). B.. Stabilization of topoisomerase-mediated cleavable complex was analysed by the immunoband depletion assay. Panel I: immunoband depletion of L. donovani topoisomerase I using an antibody raised against LdTOP1S. Leishmanial cells were treated with 0.2% DMSO alone (lane 1); with 10 and 20 µM of niranthin (lanes 3 and 4); 50 µM CPT (lane 2) and 25 µM DHBA before treatment with niranthin (lanes 6 and 7) or CPT (lane 5). Panel II: immunoband depletion of L. donovani topoisomerase II using an antibody raised against ATPase domain of L. donovani topoisomerase II. The cells were treated with 0.2% DMSO alone (lane 1) or with 10, 20 and 50 µM niranthin (lanes 3–5); 50 µM of CPT (lane 2) and 10 and 25 µM etoposide (lanes 6 and 7). Panel III: β-tubulin served as loading control. C.. Cleavage reaction and agarose gel electrophoresis were performed as described in the Experimental section. Lane 1, 50 fmol of pHOT1 DNA; lane 2, with 100 fmol LdTOP1LS; lane 3, same as lane 2, but with SDS–proteinase K treatment; lanes 4 and 5, same as lane 3, but in the presence of 25 and 50 µM CPT, respectively, as control; lanes 6–10, same as lane 3, but in the presence of 2, 5, 10, 25 and 50 µM niranthin; lanes 11–14, same as lane 2, but the enzyme was pre-incubated with 1, 5, 10 and 25 µM DHBA before addition of niranthin (25 µM) and DNA. Positions of supercoiled monomer (SM; form I) and nicked monomer (NM; form II) are indicated. Form I′, relaxed molecules. Download figure Download PowerPoint To support the notion of covalent complex formation between topoisomerase I and DNA in intact cells, we carried out immunoband depletion experiments with L. donovani promastigotes. Nuclear fractions were prepared from untreated as well as drug-treated promastigotes and subjected to SDS–PAGE. If topoisomerase I can form a covalent complex with genomic DNA inside cells, this topoisomerase I–DNA covalent complex cannot penetrate into the gel. On the other hand, if topoisomerase I does not form a complex with DNA and remains free, it will enter into the gel. The immunoband of topoisomerase I gradually disappeared with increasing concentration of niranthin during an 8 h incubation (Fig 2B, panel I, lanes 3 and 4) similar to treatment with 50 µM of CPT for 8 h (lane 2). Pre-incubation with 20 µM of DHBA before treatment with niranthin (Fig 2B, panel I, lanes 6 and 7) prevents immunoband depletion of L. donovani topoisomerase I as cleavable complex formation is prevented. The same experiment was performed with an antibody against LdTOP2 to investigate if niranthin could enhance in vivo cleavable complex formation by topoisomerase II. The topoisomerase II immunoband was not depleted by increasing the concentration of niranthin (10–50 µM) during the same time period of incubation (Fig 2B, panel II, lanes 3–5) compared to treatment with etoposide (Fig 2B, panel II, lanes 6 and 7), which is a known topoisomerase II poison. The above results suggest that niranthin treatment leads to stabilization of topoisomerase I–DNA cleavable complex formation inside leishmanial cells. To further investigate the cleavage complex stabilization by niranthin, in vitro plasmid cleavage reactions were performed under equilibrium conditions by reacting LdTOP1LS with pHOT1 DNA, which harbours a topoisomerase IB-specific binding site, in the presence of niranthin and CPT (Fig 2C) in presence of increasing concentrations of either CPT or niranthin. We observed that closed circular DNA (form I) was converted to nicked circular DNA (form II) in presence of 100 fmol of LdTOP1LS with increasing drug concentrations (Fig 2C, lanes 6–10). The formation of form II DNA in the presence of topoisomerase I only is shown in lane 3. This result shows that niranthin does not inhibit the cleavage step of the topoisomerase I-catalysed reaction, but stabilizes the topoisomerase I-mediated cleavable complex and acts as a topoisomerase poison. Furthermore, addition of increasing concentrations of DHBA prior to the addition of 25 µM of niranthin (Fig 2C, lanes 11–14) caused inhibition of niranthin-mediated plasmid cleavage. The above observation was also supported by duplex oligonucleotide cleavage assay (Supporting Information Fig S2) where the stabilization of a covalent complex (formed by niranthin) between 25-mer duplex DNA and LdTOP1LS was similar to that of CPT. Catalytic assays do not allow a precise chronological dissection of the inhibitory mechanism in relation to the catalytic cycle. Thus, the step at which an inhibitor needs to enter the catalytic cycle, and the step at which it becomes effective in trapping or inhibiting the enzyme cannot be differentiated. In order to overcome this problem, we generated an oligonucleotide suicide substrate of topoisomerase IB, which restricts the enzyme to a single round of cleavage and religation and allows for addressing the two half-reactions separately as we have described previously (Das et al, 2006). Like CPT, niranthin inhibits the religation reaction, when added to the enzyme substrate covalent complex that had been previously formed in the absence of the drug (Supporting Information Fig S3, lanes 10 and 11) after the suicidal cleavage reaction. These data suggest that the interaction of niranthin with the enzyme during the trans-esterification reaction with DNA is a pre-requirement for the stabilization of the topoisomerase I-cleavable complex. Niranthin inhibits the catalytic activity of L. donovani topoisomerase IB and acts like a non-competitive inhibitor The overall effect of niranthin on the unusual bi-subunit type IB topoisomerase of L. donovani (LdTOP1LS) was examined by plasmid relaxation assays in which the molar ratio of plasmid DNA and enzyme was 3:1. Under this condition in absence of any inhibitor, LdTOP1LS relaxes supercoiled plasmid DNA completely after 20 min of incubation (Roy et al, 2008). The inhibition of this reaction by niranthin increases in a dose-dependent manner (Fig 3A, lanes 9–16). At 25 µM, almost 85% inhibition was achieved (Fig 3A, lane 13) while 98% inhibition was achieved by 50 µM niranthin (lane 14). Figure 3. Inhibition of relaxation assay by niranthin. A.. Relaxation of supercoiled pBS (SK+) DNA with reconstituted LdTOP1LS at a molar ratio of 3:1. Lane 1, 90 fmol of pBS (SK+) DNA; lane 2, same as lane 1, but simultaneously incubated with 30 fmol of LdTOP1LS for 30 min at 37°C; lane 3, same as lane 2, but in presence of 2% v/v DMSO; lanes 4–8, same as lane 2, but in presence of 2, 5, 10, 25 and 50 µM of CPT, respectively; lanes 9–16, same as lane 2, but in presence of 1, 2, 5, 10, 25, 50, 100 and 200 µM of niranthin, respectively. B.. Preincubation of LdTOP1LS with respective inhibitors followed by addition of DNA. Lane 1, 90 fmol of pBS (SK+) DNA; lanes 2 and 3, same as lane 1, but DNA was added after preincubation of 30 fmol LdTOP1LS with reaction buffer and with 2% DMSO, respectively, for 5 min at 37°C; lanes 4–8, same as lane 2, but the enzyme was pre-incubated with 2, 5, 10, 25 and 50 µM CPT, respectively; lanes 9–16, same as lane 2, but the enzyme was pre-incubated with 1, 2, 5, 10, 25, 50, 100 and 200 µM niranthin, respectively. C.. Quantitative representation of enzyme inhibition as a function of inhibitor concentrations in presence of niranthin in relaxation experiments. The fitted lines (sigmoidal) from these data points (n = 3) have the R2 values of 0.9828 and 0.9793 respectively. D.. Lineweaver–Burk representation of the kinetics of relaxation of negatively supercoiled pBS (SK+) DNA by LdTOP1LS alone (•) or with 5 µM (▴) and 25 µM (♦) of niranthin. Download figure Download PowerPoint To investigate the interaction of niranthin with the enzyme in this relaxation experiment, LdTOP1LS was pre-incubated with niranthin at different concentrations prior to addition of substrate plasmid DNA (Fig 3B). The inhibition of LdTOP1LS by pre-incubation with niranthin was compared with the inhibitory effects of niranthin incubated simultaneously with the enzyme and supercoiled DNA in the relaxation assay. Under these conditions, 85% inhibition was achieved at 10 µM niranthin (Fig 3B, lane 12) and 98% inhibition at 25 µM (Fig 3B, lane 13). The percentage of inhibition of relaxation was plotted against the concentration of the compounds for both simultaneous and preincubation assay conditions (Fig 3C). The IC50 values of niranthin in simultaneous and pre-incubation DNA relaxation assay were 4.86 and 1.52 µM, respectively, using the variable slope model, which fits the nonlinear regression equation. Camptothecin, the well established inhibitor of LdTOP1LS, acts as a non-competitive inhibitor of topoisomerase IB (Roy et al, 2008). The above pre-incubation relaxation assay and cleavage experiment suggest that niranthin interacts with the DNA-bound as well as the free enzyme. To further investigate the inhibition of LdTOP1LS by niranthin, a time course relaxation experiment was performed in which the concentration of supercoiled substrate pBS (SK+) DNA was varied over a range of 8–60 nM. The velocity of the enzyme remains linear for the first 5 min of reaction and all the subsequent velocities for this kinetic study were measured for up to 1 min, which falls within the linear range for the velocity examined. The initial velocities for each substrate concentration were plotted in a Lineweaver–Burk plot (Fig 3D). The maximal velocity (Vmax) for the LdTOP1LS was 6.37 × 10−8 M base pairs of supercoiled DNA relaxed/min/0.98 nM of enzyme, which corresponds to a turnover of about 65 plasmid molecules relaxed/min/molecules of enzyme and is reduced upon the incubation of different concentrations of niranthin with LdTOP1LS. Niranthin binds the enzyme in reversible manner and interacts with each subunit of LdTOP1LS in equimolar fashion The inhibition of the relaxation reaction after pre-incubation as described above supports that niranthin interacts with the enzyme. However, it remained unclear whether the interaction is strong enough so that they can act on the enzyme in an irreversible manner. This critical issue was investigated in a dilution experiment. Reconstituted LdTOP1LS was preincubated with 20 µM of niranthin (Fig 4A, lane 4), the concentration at which 95–99% inhibition of enzyme activity has been achieved. The reaction mixtures were subsequently diluted fivefold so that the final concentration was 4 µM niranthin at which partial (about 30%) relief of inhibition was observed (Fig 4A, lane 5). Further 10-fold (Fig 4A, lane 6) and 20-fold (Fig 4A, lane 7) dilution resulted in almost 80% and complete relief of inhibition, respectively. In the drug control reaction, i.e. inhibition with 1 µM niranthin showed the expected pattern of inhibition (Fig 4A, lanes 8). Thus, the relief of inhibition upon dilution suggests that niranthin acts in reversible fashion against LdTOP1LS. Figure 4. Reversible and weak interaction between nirathin and LdTOP1LS. A.. Niranthin binds with LdTOP1LS in reversible manner. Lane 1, 50 fmol of pBS (SK+) DNA. Lane 2, LdTOP1LS (100 fmol) incubated at 37°C for 3 min in the reaction mixture before addition of pBS (SK+) DNA. Lane 3, same as lane 2,